Fraglilitas Eritrosit Anjing Lokal Bali (THE FRAGILITY OF ERYTHROCYTE ON LOCAL DOGS IN BALI) - Siswanto Siswanto; I Gusti Agung Arta Putra; Ida Ayu Putri Utami; I Gede Soma (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2001)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text